Preparation and Characterization of Polyethylene Biocomposites Reinforced by Rice Husk: Application as Potential Packaging Material - Emi Govorcin Bajsic; Ana Persic; Tomislav Jemric; Josip Buhin; Dajana Kucic Grgic; Emilija Zdraveva; Krunoslav Zizek; Tamara Holjevac Grguric (Chemistry, 2021)
The development of biodegradable materials as food packaging material is important not only due to the reduction in environmental pollution but also because of an improvement in the functionality. Rice husk-reinforced biopolymers have offered a possible solution to waste-disposal problems associated with traditional petroleum-derived plastics. Rice husk-reinforced low density polyethylene (LDPE)-based biocomposites have been of great interest for their use as food packaging material. In this work, the LDPE/RH biocomposites with different rice husk (RH) content (10, 20, 30, 40 and 50 wt.%) were prepared by the melt mixing process in a laboratory Brabender mixer. The effect of RH content on the physical, thermal and mechanical properties of LDPE was investigated. More importantly, this work aimed to research the biodegradation of the LDPE/RH biocomposites as well as their effect on ‘Granny Smith’ apples’ respiration. The results showed that the incorporation of RH into the LDPE decreased the thermal stability of LDPE, increased water vapour permeability and water absorption, and increased the degree of crystallinity. The incorporation of RH increased the biodegradability of LDPE as well as the postharvest quality of ‘Granny Smith’ apples. The addition of RH in LDPE film significantly decreased fruit respiration and increased firmness as compared to LDPE film. The composting results showed that after the LDPE/RH biocomposite films were biodegraded for 21 days, the biocomposite films with the highest content of rice husks were the most degraded.